2019
DOI: 10.1002/hep4.1303
|View full text |Cite
|
Sign up to set email alerts
|

IL‐22 and IL‐22‐Binding Protein Are Associated With Development of and Mortality From Acute‐on‐Chronic Liver Failure

Abstract: Interleukin‐22 (IL‐22) has context‐dependent hepatoprotective or adverse properties in vitro and in animal models. IL‐22 binding protein (IL‐22BP) is a soluble inhibitor of IL‐22 signaling. The role of IL‐22 and IL‐22BP in patients with acute‐on‐chronic liver failure (ACLF) is unclear. Beginning in August 2013, patients with liver cirrhosis with and without ACLF were prospectively enrolled and followed at predefined time points. IL‐22 and IL‐22BP concentrations were quantified and associated with clinical endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…9 In humans it was demonstrated that lower IL-22BP levels in alcoholic hepatitis were associated with increased mortality. 10 More recently, these results were replicated in a larger cohort of patients with cirrhosis and ACLF, where low IL-22BP/IL-22 ratio and high IL-22 levels were associated with adverse outcome, 11 as IL-22 signalling may not only be pro-regenerative but also induce hepatocellular production of acute-phase proteins, thus augmenting proinflammatory responses. 12 The interaction with IL-22BP will need to be carefully monitored in any prospective human studies.…”
Section: Il22-stat3 Pathway Promotes Tissue Regeneration In Aclfmentioning
confidence: 84%
“…9 In humans it was demonstrated that lower IL-22BP levels in alcoholic hepatitis were associated with increased mortality. 10 More recently, these results were replicated in a larger cohort of patients with cirrhosis and ACLF, where low IL-22BP/IL-22 ratio and high IL-22 levels were associated with adverse outcome, 11 as IL-22 signalling may not only be pro-regenerative but also induce hepatocellular production of acute-phase proteins, thus augmenting proinflammatory responses. 12 The interaction with IL-22BP will need to be carefully monitored in any prospective human studies.…”
Section: Il22-stat3 Pathway Promotes Tissue Regeneration In Aclfmentioning
confidence: 84%
“…Recently, high levels of IL-22 have been associated with mortality from acute-onchronic liver failure, probably reflecting the severity of the disease. (36) The efficacy of IL-22 in mitigating liver injury induced by alcohol, carbon tetrachloride (CCl 4 ), or a high-fat diet has been demonstrated in animal models. (15,(37)(38)(39)(40) The IL-22 agonist's safety profile and unique biology, which specifically targets epithelial cells, suggests its potential use as monotherapy in patients with AH and MELD scores of 11-28.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we agree with the hypothesis by Schwarzkopf et al that the ineffective hepatoprotection by endogenous IL-22 in patients with ACLF may be due to high levels of IL-22BP. 1,3 However, the pharmacological treatment with IL-22Fc, which was the focus of our study, caused a several thousand-fold increase in serum IL-22 (~700,000 pg/ml after IL-22Fc vs.~200 pg/ml before IL-22Fc) and great biological responses in healthy volunteers 6,7 to an immunoglobulin constant region (IgG-Fc) and has a long half-life in vivo. 6,7 Such high levels of IL-22Fc can probably overcome the inhibitory function of IL-22BP and ameliorate ACLF by activating the pro-regenerative STAT3 signaling in hepatocytes.…”
mentioning
confidence: 84%
“…The first question raised relates to the role of endogenous interleukin (IL)-22 and IL-22 binding protein (IL-22BP) in acuteon-chronic liver failure (ACLF). Serum levels of IL-22 are elevated in patients with ACLF 1 and in mouse models of ACLF induced by infection of adenovirus-CYP4502D6 plus injection of cecal slurry (CS) or chronic CCl 4 plus 2 binges of ethanol. 2 Actually, we also found that serum IL-22 levels were mildly but significantly elevated in our ACLF model, which was illustrated in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation